2011
DOI: 10.1532/hsf98.20101179
|View full text |Cite
|
Sign up to set email alerts
|

Aortoesophageal Fistula Secondary to Thoracic Endovascular Aortic Repair of a Descending Aortic Aneurysm Rupture

Abstract: AEF is a catastrophic complication of TEVAR. Conservative treatment is often associated with fatal results. If possible, these patients should be treated with secondary major surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…3 In addition, the administration of early parenteral nutrition aggravated rather than reduced muscle weakness in the sickest patients requiring prolonged intensive care. 4 Third, a retrospective analysis showed that it was the dose of amino acids, not the amount of glucose, that explained the harm evoked by early parenteral nutrition, an observation that is completely in line with the results from a study of experimentally induced critical illness in rabbits. .…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…3 In addition, the administration of early parenteral nutrition aggravated rather than reduced muscle weakness in the sickest patients requiring prolonged intensive care. 4 Third, a retrospective analysis showed that it was the dose of amino acids, not the amount of glucose, that explained the harm evoked by early parenteral nutrition, an observation that is completely in line with the results from a study of experimentally induced critical illness in rabbits. .…”
mentioning
confidence: 53%
“…1,2 In particular, Young et al are incorrect to conclude that there has been a "not so marked" U.S. decline on the basis of economy-wide inflation, when U.S. biomedical R&D inflation is known. 3,4 Similarly, their suggestion to use GDP PPP is flawed, because costs of domestic biomedical R&D activities and corresponding PPP are unknown. Decade-long analyses of R&D-specific prices show that "at the industry level, use of GDP PPP as a proxy for R&D PPP is inappropriate."…”
Section: The Authors Replymentioning
confidence: 99%
“…In particular, a single study 14 including patients from multiple centers was excluded from the present review as many of the recruited patients were described previously in separate, more detailed publications with individualized data. Overall, 21 studies 3,4,6,9,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] (six retrospective cohort studies/case series, 15 case reports) with a total of 55 patients with thoracic endograft infection treated with endograft preservation (group A, Tables I and II) and 20 studies 3,5-8, [10][11][12]15,25,26,[32][33][34][35][36][37][38][39][40] (seven retrospective cohort studies/case series, 13 case reports) with a total of Tables III and IV) were included in this review. Demographics and comparisons between the two groups are presented in Table V.…”
Section: Resultsmentioning
confidence: 99%
“…A previous meta-analysis study described that the recurrence of AEF and graft infection after TEVAR occurred in 13.8 and 15.2% of the patients, respectively [28], and that prolonged ineffective administration of intra-venous anti-biotic medicine was the most significant factor associated with a lower mortality in the multi-variate analyses, despite the lack of definitive strategies for post-operative anti-biotic usage. Previous studies pointed out that the outcome of conservative management alone after TEVAR might be fatal due to recurrent hemorrhage or sepsis [26,28,40,[68][69][70][71][72]. Accordingly, TEVAR should be performed only as a bridging treatment before radical surgery is planned to treat the inflamed lesions of AEF patients [69].…”
Section: Controlling Fatal Bleeding From Aefmentioning
confidence: 99%